Sistem Informasi Akademik Berbasis Web Pada SMAN-1 Pulau Malan Kabupaten Katingan - Parhusip, Jadiaman; Sylvana, Felicia; Wiltra, Wiltra (STMIK Palangkaraya, 2018)
Sekolah Menengah Atas Negeri (SMAN) 1 Pulau Malan in Katingan Regency has processed data of students and teachers using computer (Microsoft Excel application) and still manage and record the attendance list and students’ grades manually using a book. This habit is considered not effective and may cause problems in calculating students’ grades. Data searching needs much time and important documents or notes are easy to disappear. This system is developed using waterfall methodology. Researcher constructs Data Flow Diagram, Entity Relationship Diagram, and designing the user interface. The functional system is tested using black box. The result of Web Based Academic Information is the availability of a computerized data processing of teachers, students, and academic. Teachers also can to calculate students’ grade, processing students’ presence per meeting, showing students’ grade, downloading subject material, showing school’s schedule and processing data account such as changing password and taking a self picture.